Targeted discovery of gut microbiome-remodeling compounds for the treatment of systemic inflammatory response syndrome - Luyao Liu; Lin Ma; Huan Liu; Fan Zhao; Pu Li; Junhua Zhang; Xin Lü; Xin Zhao; Yanglei Yi (mSystems)
ABSTRACT Systemic inflammatory response syndrome (SIRS) is a severe inflammatory response that can lead to organ dysfunction and death. Modulating the gut microbiome is a promising therapeutic approach for managing SIRS. This study assesses the therapeutic potential of the Xuanfei Baidu (XFBD) formula in treating SIRS. The results showed that XFBD administration effectively reduced mortality rates and inflammation in SIRS mice. Using 16S rRNA sequencing and fecal microbiota transplantation (FMT), we substantiated that the therapeutic effects of XFBD are partly attributed to gut microbiota modulation. We conducted in vitro experiments to accurately assess the gut microbiome remodeling effects of 51 compounds isolated from XFBD. These compounds exhibited varying abilities to induce a microbial structure that closely resembles that of the healthy control group. By quantifying their impact on microbial structure and clustering their regulatory patterns, we devised multiple gut microbiome remodeling compound (GMRC) cocktails. GMRC cocktail C, comprising aucubin, gentiopicroside, syringic acid, gallic acid, p-hydroxybenzaldehyde, para-hydroxybenzoic acid, and isoimperatorin, demonstrated superior efficacy in treating SIRS compared to a single compound or to other cocktails. Finally, in vitro experiments showcased that GMRC cocktail C effectively rebalanced bacteria composition in SIRS patients. This study underscores XFBD’s therapeutic potential in SIRS and highlights the importance of innovative treatment approaches for this disease by targeting the gut microbiota.IMPORTANCEDeveloping effective treatment strategies for systemic inflammatory response syndrome (SIRS) is crucial due to its severe and often life-threatening nature. While traditional treatments like dexamethasone have shown efficacy, they also come with significant side effects and limitations. This study makes significant strides by demonstrating that the Xuanfei Baidu (XFBD) formula can substantially reduce mortality rates and inflammation in SIRS mice through effective modulation of the gut microbiota. By quantitatively assessing the impact of 51 compounds derived from XFBD on the gut microbiome, we developed a potent gut microbiome remodeling compound cocktail. This cocktail outperformed individual compounds and other mixtures in efficacy against SIRS. These findings highlight the potential of XFBD as a therapeutic solution for SIRS and underscore the critical role of innovative strategies targeting the gut microbiota in addressing this severe inflammatory condition.